Effects of UV-B light exposure during automatic milking on vitamin D levels in Holstein Friesian cows - Hodnik, Jaka Jakob; Jankovec, Marko; Ježek, Jožica; Krušič, Žiga; Mitterhofer, Stefan; Starič, Jože (Frontiers in Veterinary Science, 2025)
Vitamin D is essential for cattle and can be synthesized in the skin under ultraviolet irradiation. This study investigated the effects of narrow-band UV-B irradiation during automatic milking on blood vitamin D concentration and the influence of hair and black skin areas on cutaneous vitamin D synthesis in Holstein Friesian cows. Fifty-one cows were stratified by milk yield, days after calving, and percentage of black skin, then divided into three groups: shaved and irradiated (80 J/m2), unshaved and irradiated (129–305 J/m2), and a control group. A custom UV-B light (peak radiation at 295 nm) was installed in the milking robot. Blood 25-hydroxyvitamin D (25(OH)D) levels were measured at baseline, and 7, 30, and 60 days post-exposure using an enzyme-linked fluorescent assay. UV-B exposure significantly (p < 0.001) increased 25(OH)D levels in shaved (13.4 ng/mL), unshaved (10 ng/mL), and control groups (5.1 ng/mL). Despite receiving less than half the UV-B dose, the shaved group had superior 25(OH)D synthesis compared to the unshaved group (p < 0.05), highlighting hair’s role in reducing UV-B absorption. Cutaneous synthesis correlated with black skin area in shaved cows but not in unshaved cows. UV-B irradiation also increased daily milk production by 2.2 kg (shaved) and 2.9 kg (unshaved) compared to controls (p < 0.001). UV-B exposure during automatic milking offers a novel, non-disruptive method for enhancing vitamin D levels in dairy cows.